Where's that bomb? On guard for Spain (leaflet)
042-0066-001 Saturday, February 19th 8.15 p.m. at the UNITY THEATRE GOLDINGTON ST., ST. PANCRAS Telephone : Euston 5391 A Special Programme — " Where's That Bomb?" " On Guard For Spain " Items by Dance Drama Group Mrs. Cecil Chesterton will be the guest of honour and will speak during one of the intervals Proceeds for Spanish Medical Aid TICKETS : 1/-, 1/6, 2/6 or 3/6, direct from the Theatre. Members and Associates only. Printed at the FARLEIGH PRESS (T.U. all depts.), 17-29 Cayton Street, London, E.C.1. 292/946/42/66